2016
DOI: 10.1016/j.semcdb.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac connexome: Non-canonical functions of connexin43 and their role in cardiac arrhythmias

Abstract: Connexin43 is the major component of gap junctions, an anatomical structure present in the cardiac intercalated disc that provides a low-resistance pathway for direct cell-to-cell passage of electrical charge. Recent studies have shown that in addition to its well-established function as an integral membrane protein that oligomerizes to form gap junctions, Cx43 plays other roles that are independent of channel (or perhaps even hemi-channel) formation. This article discusses non-canonical functions of Cx43. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…A loss-of-function study indicates that another property of Cx43, other than its ability to form gap junctions, appears to be responsible for its indispensability in germ line development [174,176]. Moreover, recent studies have reported additional functions of Cxs, such as regulating gene transcription and interacting with cell growth and cell death modulators, as well as having chemical roles [177][178][179]. Thus, further research on the different functions of Cx43 is required.…”
Section: Discussionmentioning
confidence: 99%
“…A loss-of-function study indicates that another property of Cx43, other than its ability to form gap junctions, appears to be responsible for its indispensability in germ line development [174,176]. Moreover, recent studies have reported additional functions of Cxs, such as regulating gene transcription and interacting with cell growth and cell death modulators, as well as having chemical roles [177][178][179]. Thus, further research on the different functions of Cx43 is required.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, it was recently demonstrated that the formation of Cx43 gap junction channels between cardiomyocytes and tissue-resident macrophages facilitates electrical conduction through the distal atrioventricular node (Hulsmans et al, 2017). Furthermore, a new concept emerging in the field is that the coordinated propagation of action potential in the heart relies not solely on gap junctions, but also on the profile of proteins found within the Cx43-scaffold at the intercalated disc, the so-called 'cardiac connexome' (Leo-Macias et al, 2016). In fact, a specific pool of undocked connexons that are localized to the periphery of a gap junction plaque ('the perinexus'), rather than contributing to gap junction formation, serves to maintain interactions with a network of proteins, such as the desmosomal protein plakophilin-2, the cytoskeletal adaptor protein ankyrin-G and the pore-forming subunit of the cardiac Na + channel Na v 1.5 (formed from protein SCN5A) (Rhett and Gourdie, 2012;Sato et al, 2011).…”
Section: The Role Of Gjic In the Heartmentioning
confidence: 99%
“…Members of this family (21 members in humans) typically form gap junction intercellular channels, allowing for the direct cell-to-cell transfer of small molecules, including second messengers, but Cxs can also assemble into undocked hemichannels that open transiently to release extracellular signals (Goodenough and Paul, 2009; Evans, 2015). In addition, Cxs may contribute to signaling that is independent from their channel function, by functionally interacting with other vital cellular proteins (Laird, 2010; Zhou and Jiang, 2014; Leo-Macias et al, 2016). …”
Section: Introductionmentioning
confidence: 99%